Endotoxemia-Induced Release of Pro-inflammatory Mediators Are Associated With Increased Glomerular Filtration Rate in Humans in vivo - Beunders, Remi; Schütz, Maren J.; van Groenendael, Roger; Leijte, Guus P.; Kox, Matthijs; van Eijk, Lucas T.; Pickkers, Peter (Frontiers in Medicine, 2020)
Introduction Sepsis is the most prevalent cause of Acute Kidney Injury (AKI). Conversely, in some septic patients the glomerular filtration rate (GFR) is augmented. The role of the inflammatory response and blood pressure to induce this increased GFR is unknown. Herein, relate inflammatory mediators and blood pressure to the ‘true’ GFR measured using iohexol clearance and kidney injury markers during systemic inflammation in healthy volunteers. Methods and Methods Twelve healthy subjects underwent experimental endotoxemia (i.v. administration of 2 ng/kg Escherichia coli-derived lipopolysaccharide, LPS). As a gold-standard to determine the GFR, iohexol plasma clearance (GFRiohexol) was calculated during a 6-hour period on the day before (baseline) as well as 2 and 24 hours after LPS administration. Intra-arterial blood pressure was recorded continuously using a radial artery catheter. Circulating inflammatory mediators and urinary excretion of kidney injury markers were serially measured. Results Experimental endotoxemia profoundly increased plasma concentrations of inflammatory mediators, including (mean±SD or median [IQR] peak values (pg/mL) of tumor necrosis factor (TNF)-α: 92±40, interleukin (IL)-6: 1246±605, IL-8: 374±120, IL-10: 222±119, IL-1 receptor antagonist (RA): 8955±2429, macrophage chemoattractant protein (MCP)-1: 2885 [2706-3765], vascular adhesion molecule (VCAM)-1: 296105±34822, intercellular adhesion molecule (ICAM)-1: 250170±41764). Mean arterial pressure decreased with 13±11 mmHg (p<0.0001). No significant increase in the urinary excretion of tubular injury markers was observed following LPS administration. GFRiohexol¬ increased from 97±6 at baseline to 118±10 mL/min/1.73m2 (p<0.0001) post-LPS administration and returned to baseline levels at 24 hours post-LPS (99±9 mL/min/1.73m2). Peak plasma concentrations of IL-6 (R2=0.66, p=0.001) and IL-8 (R2=0.51, p=0.009), MCP-1 (R2=0.38, p=0.03) and VCAM-1 levels (R2=0.37, p=0.04) correlated with the increase in GFRiohexol¬, whereas a trend was observed for TNF-α (R2=0.33, p=0.0509) and IL-1RA (R2=0.28, p=0.08). None of the kidney injury markers or changes in blood pressure were associated with the GFRiohexol¬. In multiple linear regression analysis, both peak IL-6 (p=0.002) and IL-8 (p=0.01) concentrations remained significantly correlated with GFRiohexol, without collinearity. Discussion Concentrations of pro-inflammatory cytokines, but not blood pressure, are correlated with the endotoxemia-induced increase in GFR in healthy volunteers. These findings suggest that inflammatory mediators account for the increased GFR observed in a subgroup of sepsis patients.